1991
DOI: 10.1177/00220345910700030601
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Magnesium in Developing Rat Incisor Dentin

Abstract: Previous studies have shown that rat incisor dentin contains a considerable amount of magnesium that is distributed heterogeneously. The cementum-related dentin, especially its incisal portion, is richest in magnesium. It was the purpose of the present study to investigate the changes that occur in the magnesium content during dentin maturation.Cross-sections were prepared from rat incisors at the apical, middle, and incisal levels. By means of an electron microprobe, tracings were made of the Ca-, Mg-, and P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…This could be interpreted to suggest that in the odontoblasts which also express CNNM4 [1,4], the defect of the protein impairs the transport of Mg into the tissue. As Mg of the dentin mineral is believed to compete with Ca and to be bound to phosphate [15], the observed slightly increased Ca content would also appear to agree with this assumption.…”
Section: Discussionmentioning
confidence: 57%
“…This could be interpreted to suggest that in the odontoblasts which also express CNNM4 [1,4], the defect of the protein impairs the transport of Mg into the tissue. As Mg of the dentin mineral is believed to compete with Ca and to be bound to phosphate [15], the observed slightly increased Ca content would also appear to agree with this assumption.…”
Section: Discussionmentioning
confidence: 57%
“…The inductive analysis also showed that Mg was the most important element for discrimination of hypomineralized from normal enamel. Animal studies have shown that increased levels of Mg in enamel at late developmental stages may delay mineralization, resulting in poorly crystallized enamel (Spencer et al, 1989;Steinfort et al, 1991). Normal enamel shows consistent gradients similar to that seen for Na, whereas MIH enamel shows inconsistent trends.…”
Section: Discussionmentioning
confidence: 95%
“…Oim/+ tibias of both strains are intermediate to Wt and oim/oim in both fluoride levels and biomechanical integrity. Magnesium, thought to inhibit crystal formation by competing with calcium and blocking the active crystal growth sites [49,50], also demonstrated a negative association with bone strength and energy to failure. Fratzl et al demonstrated that oim/oim cortical bone has thinner and less well aligned crystals, contributing to the reduced strength of the bone [51].…”
Section: Discussionmentioning
confidence: 99%